Lipid Peroxidation of Escherichia coli by Triplet Non-thermal Atmospheric Pressure Plasma Jet - A. Hossienzadeh Colagar (Science Faculty of Chiang Mai University, 2019)
Non-thermal atmospheric plasma can be applied for sterilization of contaminated surfaces. The purpose of the present work is to study the bactericidal effects of non-thermal plasma on Escherichia coli and determine the level of malondialdehyde (MDA). In the present study, a non-thermal argon/air plasma jet was used to sterilize the Escherichia coli on solid surfaces and broth medium. The plasma jet was supplied by a sinusoidal high voltage at 18.56 kHz. Bacterial sterilization assayed by measurement of the growth inhibition zones and turbidimetry analysis in solid and broth media, respectively. The levels of MDA were measured at different time durations by thiobarbituric acid-reactive substance (TBARS) method. The study showed that increasing the exposure time leads to the extension of disinfection zone. Furthermore, MDA concentration was increased in more exposure times. It was concluded that the plasma jet could completely reduce survival of E. coli with 2´108 colony-forming units per ml after 10 minutes on broth medium. Such a plasma jet can be a promising device for disinfection and sterilization of bacteria in hospitals and the food industry.